Study of Preferences and Economic Aspects of Low-Income Housing Development (LIC) in Batangkuis Sub-District - Azhar, Khairul; M Siahaan, Nelson; Marisa, Ami (Universitas Ibn Khaldun Bogor, 2024)
The rapid growth and development of major cities in Indonesia has resulted in regional growth and the formation of a class of Low-Income Communities (LIC) and the problem of providing housing for them. This study was conducted to identify the preferences of low-income housing ownership as well as to examine the development of low-income housing in terms of economic aspects. A quantitative approach was taken for LIC home ownership preferences and qualitative for LIC housing development prospects from an economic aspect. The results showed that home ownership preferences and the willingness of LIC to pay for housing units were influenced by variables of residential typology in the form of a single detached house, affordable prices with the ability to pay for LIC, convenient location, provision of basic housing facilities and infrastructure, good quality with attractive designs without affecting the price and supported by the availability of financing institutions that provide installment scheme facilities. LIC housing development in Batangkuis District in terms of economic aspects shows promising prospects in terms of supply by developers where land prices and financing along with construction costs as well as licensing and other legalities are still below the selling price set by the government. The availability of banking financing institutions that help facilitate financing also supports developers in marketing and sales. Meanwhile, from the side of LIC consumers in Batangkuis Sub-district, the availability of financing institutions has no effect because of the gap between the concept of financing and their economic capacity. The amount of monthly installments and initial financing is quite large, making them unable to access subsidized LIC housing developed in Batangkuis District.